2017
DOI: 10.2196/jmir.7564
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Interventions to Improve Mental Health, General Caregiving Outcomes, and General Health for Informal Caregivers of Adults With Chronic Conditions Living in the Community: Rapid Evidence Review

Abstract: BackgroundMost adults with chronic conditions live at home and rely on informal caregivers to provide support. Caregiving can result in negative impacts such as poor mental and physical health. eHealth interventions may offer effective and accessible ways to provide education and support to informal caregivers. However, we know little about the impact of Web-based interventions for informal caregivers of community-dwelling adults with chronic conditions.ObjectiveThe purpose of this rapid evidence review was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
123
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(137 citation statements)
references
References 43 publications
7
123
0
1
Order By: Relevance
“…Google analytics demonstrated that demand for the resource was good with 2800 visits within 6 months and 750 repeat visits, of these repeat visitors 70% visited the site multiple times. Set in the context of 9000 new cancer cases per year in Northern Ireland, a high usage trend supports the evidence that carers regularly access web‐based information . The majority of visitors were directed to the site via Facebook and Google and accessed via a mobile device.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Google analytics demonstrated that demand for the resource was good with 2800 visits within 6 months and 750 repeat visits, of these repeat visitors 70% visited the site multiple times. Set in the context of 9000 new cancer cases per year in Northern Ireland, a high usage trend supports the evidence that carers regularly access web‐based information . The majority of visitors were directed to the site via Facebook and Google and accessed via a mobile device.…”
Section: Discussionmentioning
confidence: 58%
“…9 Interventions targeted at the cancer carer can improve outcomes such as quality of life and caregiver burden, [14][15][16][17][18][19] in particular those utilizing technology and a self-directed format. 20 A review of web-based interventions for carers across various chronic illnesses found positive changes in psychological health, knowledge, and relationships; however, much of the quality of these studies were deemed as methodologically weak, and therefore more work on the subject is needed. 20 It is argued that the best way to ensure that interventions meet the needs of the target population is to involve stakeholders in design and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Online mode of delivery was utilised in 43% ( n = 12/28) of the studies, although representing just under half of the identified research it demonstrates that its usage is being considered as a credible method. This mode of delivery for interventions for carers of individuals living with chronic diseases other than dementia, has been shown to effectively improve self‐esteem, self‐efficacy and depression (Ploeg et al, ). Web‐based interventions in particular are beneficial for informal carers due to the 24/7 nature of caring and consequent difficulties in accessing services (Duggleby et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of extraordinary care for a person with Alzheimer's disease or other dementias to develop activities of daily living (ADLs) and instrumental activities of daily living (IADLs) resides in a person who is considered as a caregiver [1]. Sometimes the role of caregiver may be perceived as a satisfying and rewarding task [4,5]; nevertheless, providing continued support to people with dementia entails an enormous short and long term effort because of the irrepressible decline caused by the disease [6]. In addition, the task may prove difficult, requiring caregivers to face stressful and uncontrolled situations as a result of having to deal with a wide range of care conditions, some of which are very complex [7].…”
Section: Introductionmentioning
confidence: 99%